The Concept of Paradox Architecture in the Design of Hisab Ru’ya Observatory in Indonesia - Yudha, Ansfiksia Eka Poetra; Setiyowati, Ernaning; Mappaturi, Andi Baso (Proceedings of the International Conference on Green Technology, 2017)
There are two kinds of methods in determining hijriyah and qamariyah calendar that is used by Indonesian Islamic organizations. Some of them use hisab method, and the others use ru’ya . The diffference of the methods makes people has different time to start their ritual religious activities such as Ramadhan fasting and eid, while this activities are the most important moment for muslim to do their religious activities together. To solve this problem, a hisab-ru’ya observatory needs to be built to receive the Islamic Organizations’ aspiration in determining the hijriyah and qamariyah calendar. The concept design of this building is paradox architecture that will combine two different things into one to achieve one goal. This concept design is suitable with the issue and the object that needs to combine two methods to achieve one goal. The aim of this study is to apply the principle of the paradox architecture concept in the design of Hisab Ru’ya Observatory.